History of coronary surgery and the role of russian surgeons in its development - G. Sh. Garayev; K. A. Agharzayev (Вестник хирургии имени И.И. Грекова)
Ischemic heart disease is a common disease among the population. Due to the high mortality rate related to this disease, improving its treatment has always been a focal point. cardiologists, along with surgeons, have conducted multidirectional scientific researches for a long time to improve the treatment of acute coronary syndrome. Finally, in 1957, V. P. Demikhov’s experiments on dogs laid the foundation of the treatment of acute coronary syndromes.Taking advantage of this experience, in 1964, V. I. Kolesov managed to restore the impaired blood supply by connect ing the internal mammary artery to the lower part of the coronary artery from the blocked part of the coronary artery in a patient with acute coronary syndrome.This treatment method, which the author called mammary-coronary anastomosis, soon attracted the attention of a number of surgeons around the world who tried to restore the impaired blood supply to the myocardium using this method.The article provides information about researches conducted by distinguished scholars who have made significant contributions to the development of mammary-coronary anastomosis. Also, it offers more detailed information about the role of the renowned surgeon V. I. Kolesov and his school in the development of this treatment method.The refinement of the technique for performing mammary-coronary anastomosis is attributed specifically to the school of V. I. Kolesov. Under his guidance, researches conducted by his students led to the development of the technique for placing mammary-coronary anastomosis using a vascular sewing machine. This also gave rise and justified the idea of performing coronary artery surgery on a beating heart.The article also presents extensive information about a new myocardial infarction model that is suitable for demonstrat ing the dependence of myocardial blood supply restoration through mammary-coronary anastomosis on the duration of coronary artery occlusion. Even so, the article highlights the role of colleagues from the Department of Faculty Surgery № 1 at Pavlov First Saint Petersburg State Medical University in the creation and development of this method.